Ovarian tumors in childhood and adolescents - Our eight years experiences - Amatya, Archana; Rana, Ashma; Gurung, Geeta (Nepal Journal of Obstetrics and Gynaecology, 2008)
Aims: To study the distribution of different types of ovarian tumors seen in adolescents and children and evaluate the commonest tumor during this period. Methods: A prospective study conducted at Dept of Ob/Gyn, Tribhuvan University Teaching Hospital form January 1999 - January 2008. Results: There were a total of 80 cases of ovarian tumors in childhood and adolescents. Most of the cases had presented to the outpatient department of Ob/Gyn (54%), Medicine (10%), Surgery (21%) and Emergency Unit (15%). Majority of the cases were between the ages of 15 to 19 and tumors in childhood age up to 14 represented 21% of the total ( < 10year being 4). The most frequently occurring tumor was Germ cell tumors accounting for 59 (73.7%) of the total. Out of which dermoid was the most frequently occurring in 45(76.2%). Nineteen (23.71 %) of the total tumor were malignant. All of them underwent laparatomy followed by enucleation (14); Unilateral ophoorectomy (28), unilateral salphingooophorectomy (36) and TAHBSO (2). Conclusion: This study shows the preponderance of germ cell tumor and high percentages of malignancies within germ cell tumor in young children and adolescents. Keywords: childhood, adolescent, ovarian tumors, malignancy doi:10.3126/njog.v3i1.1438 NJOG 2008 May-June; 3(1): 39 - 42